Character strengths as predictors of general and academic self-efficacy in university students - García-Álvarez, Diego; Cobo-Rendón, Rubia; Lobos, Karla (Frontiers in Psychology, 2024)
Positive psychology has introduced the concept of character strengths, which are positive traits fundamental to well-being and mental health. Research on university students has shown that these strengths impact psychoeducational variables and personal functioning, acting as a protective factor in the general and student populations. This study aims to analyze the predictive relationships between character strengths and general self-efficacy and determine their joint contribution in predicting academic self-efficacy. The study was quantitative, correlational-causal, and cross-sectional, using a non-probabilistic sample of 668 Venezuelan university students (68.86% women, average age of 20.52 years). The scales used are Growing Strong to measure character strengths, the General Self-Efficacy Scale, and the Self-Efficacy Scale in Specific Academic Situations. All scales showed adequate psychometric properties. The mediation analysis revealed that leadership, hope, and persistence positively influence general and academic self-efficacy. Furthermore, general self-efficacy strongly impacts academic self-efficacy. In conclusion, character strengths are significant predictors of self-efficacy in university students. Promoting these strengths may be crucial to improving general and academic self-efficacy, suggesting the need to implement specific initiatives in higher education.